Pensando en Iberia: los debates en torno a la unificación hispano-portuguesa en el exilio republicano en México - Jorge de Hoyos Puente (Les Cahiers de Framespa)
The Spanish Republican exile is probably one of the most complex in the twentieth century. Its size, variety and duration led to many identity-forming processes, political projects and theoretical debates. Sometimes it also stimulated the revival of once-abandoned aspirations, such as that of ‘Iberism’, a nationalist movement based on the two states that existed in the Iberian peninsula and which was strongest during the nineteenth century. The assertion of the constitution of a unified peninsula was re-formulated by some elements of the Republican exile based in Mexico. This study analyses their approach to the concept of the ‘Nation’, their historically-based justifications, and their dissemination through publications such as Las Españas. We will refer to figures such as Anselmo Carretero, Ramón Xirau, Mariano Granados and Félix Gordón Ordás, among others. Iberism was a minority movement among the republican exile, but it was extremely active: it presented a pluralistic concept of Spain, that required a federal or confederal form of territorial organization.